French sinology and Gustave Caillebotte’s Portrait of Henri Cordier, 1883 - Chang, Ting (2016)
This presentation examines the competing and sometimes conflicting demands encountered in the study of portraiture and biography. Once revised, the paper will become an article that will make an original contribution to art history in empirical and conceptual ways. Based on research in unpublished archives I have discovered the nature of the relationship between the artist Caillebotte and the sitter Cordier, a previously unsolved mystery variously noted by commentators on the painting. I will further advance the discussion by moving away from Michael Fried's concept of "absorption," a persistent interpretive model even in an exhibition catalogue on Caillebotte in 2016, to examine other questions. In addition to the problems faced by both art historians and artists between portraiture (life imaging) and biography (life writing), I will examine representations of "Frenchness," and Cordier's intellectual and political work in the broader context of French imperialism in East Asia.